Language learner autonomy: Myth, magic or miracle? - Carson, Lorna (My University, 2010)
The shift in emphasis away from the processes involved in teaching languages towards the processes involved in learning languages in formal educational contexts has brought about one of the most remarkable changes to the language classroom since the communicative approach. The elaboration of the role `learner? in this paradigm frequently involves discussion of autonomy in language learning, although perhaps not in so many words. A range of terms are employed in the discourse as practitioners and researchers attempt to depict and unpick the involvement and responsibility of the learner in learning, including, inter alia, agency (van Lier, 2010; Swain, 2007), selfdetermination (Deci & Ryan, 2000; see also Sisamakis, 2006 and Carson, 2007 with reference to foreign language learning), self-regulation (Pintrich & de Groot, 1990), learner-centredness (Tudor, 1996), learner engagement (van Lier, 1996; Ohta, 2001; Corno & Mandinach, 1983) and learner empowerment (Frymier et al., 1996; Schrodt et al., 2008). The first section of this paper defines the notion of language learner autonomy, and review some key concepts ? and misconceptions ? related to this topic; the second section presents a case study of a university language programme designed to foster language learner autonomy.
Proceedings of the International Conference, 'From Teaching to Learning: Current Trends in English Language Teaching'
PUBLISHED
Macedonia
Keywords: Educational sciences; didactics; Language learner autonomy; Creative Arts Practice; International Integration; Making Ireland